The Relationship between Scar BCG and the Incidence OF Tuberculosis (TB) in TB Patients at the Basuki Rahmad Health Center, Bengkulu City, Indonesia - Yenni Sri Handayani; Ririn Arminsih Wulandari (JUMP Health (Journal of Ultimate Public Health), 2019)
Background: Mycobacterium tuberculosis is the bacterium that causes tuberculosis. WHO said the world TB rate had increased since 2014-2017. TB is a world health problem today. Bengkulu Province experienced an increase in the number of TB cases from 2015-2017. Objectives: This study aims to determine the relationship between Scar BCG and the incidence of tuberculosis in TB patients. Methods: This study uses a case control method. The population is all patients visiting the Basuki Rahmad Health Center in 2016-2017. Sample random sampling technique. Calculation of sample size of 2 proportions with previous P1 researchers using the Lemeshow formula obtained sample results 126 1: 1. Results: Of the 126 TB patients who did not have Scar as many as 54 (42.9%) and there were 72 (57.1%) Scar BCG, 69 (54.8%) male sex and 57 female sex (45.2%) people, patients who have a lack of nutritional status as many as 38 (30.2%) people and good nutritional status as many as 88 (69.8%) people, TB patients who have low education as much as 50 (39.7% ) people and those who have higher education are 76 (60.3%) people, 58 patients (46.0%) who contact home and 68 (54.0%) non-contact patients, patients <15-50 year as many as 111 (88.1%) people and patients aged> 50 years 15 (11.9%) people. There is a significant relationship between Scar BCG, nutritional status, gender with the incidence of pulmonary tuberculosis in 2016-2017 with p = 0,000 p = 0,000 and p = 0,000. And there is no significant relationship between age, education, household contact with TB incidence in 2016-2017. Counfounding Scar BCG for TB incidence is nutritional status, gender, age and household contact. Conclusion: There is a relationship between Scar BCG, nutritional status, gender with the incidence of pulmonary tuberculosis and counfounding Scar BCG with TB incidence there are 4 variables in the Basuki Rahmad Community Health Center, Bengkulu City. Recommendation: Prevention of TB can be carried out by BCG immunization, taking medication regularly.